N‐Heterocyclic Carbene–Phosphinidene Complexes of the Coinage Metals. Issue 45 (14th September 2015) - Doddi, Adinarayana; Bockfeld, Dirk; Nasr, Alexandre; Bannenberg, Thomas; Jones, Peter G.; Tamm, Matthias
Abstract: Coinage metal complexes of the N‐heterocyclic carbene–phosphinidene adduct IPr⋅ PPh (IPr=1, 3‐bis(2, 6‐diisopropylphenyl)imidazolin‐2‐ylidene) were prepared by its reaction with CuCl, AgCl, and [(Me2 S)AuCl], which afforded the monometallic complexes [(IPr⋅ PPh)MCl] (M=Cu, Ag, Au). The reaction with two equivalents of the metal halides gave bimetallic [(IPr⋅ PPh)(MCl)2 ] (M=Cu, Au); the corresponding disilver complex could not be isolated. [(IPr⋅ PPh)(CuOTf)2 ] was prepared by reaction with copper(I) trifluoromethanesulfonate. Treatment of [(IPr⋅ PPh)(MCl)2 ] (M=Cu, Au) with Na(BAr F ) or AgSbF6 afforded the tetranuclear complexes [(IPr⋅ PPh)2 M4 Cl2 ]X2 (X=BAr F or SbF6 ), which contain unusual eight‐membered M4 Cl2 P2 rings with short cuprophilic or aurophilic contacts along the chlorine‐bridged M⋅⋅⋅M axes. Complete chloride abstraction from [(IPr⋅ PPh)(AuCl)2 ] was achieved with two equivalents of AgSbF6 in the presence of tetrahydrothiophene (THT) to form [(IPr⋅ PPh)Au(THT)2 ][SbF6 ]2 . The cationic tetra‐ and dinuclear complexes were used as catalysts for enyne cyclization and carbene transfer reactions. Abstract : Dinuclear gold catalysis : Mono‐, bi‐, and tetranuclear coinage metal complexes of an N‐heterocyclic carbene–phosphinidene are reported. Chloride abstraction affords unusual eight‐membered metallacycles, which feature cuprophilic (M=Cu) and aurophilic (M=Au) interactions (see scheme; Dipp=2, 6‐diisopropylphenyl). The cationic gold(I)–phosphinidene complexes serve as active catalysts for enyne cycloisomerization and carbene transfer reactions.